Squamomelanocytic tumors: A singular case report and comprehensive review - Cristina Lopez-Llunell; Patricia Garbayo-Salmons; Marta G Cañada; Empar S Artacho; Clara Fernández-Sartorio (Wolters Kluwer Medknow Publications, 2023)
Cutaneous neoplasms from different cell types can exist within the same lesion. These can be classified into four subtypes which are collision tumour, combined tumour, colonization and biphenotypic tumour. The presence of a melanoma component in these tumours is very rare. Herein we present a singular case of two synchronous dineoplastic cutaneous tumours: a squamomelanocytic tumour and a collision consisting of melanoma and seborrheic keratosis. Additionally, we performed a literature review of all squamomelanocytic tumours published until date, including our case.